STRATEGI PENGEMBANGAN USAHA KERIPIK PISANG PADA INDUSTRI “FLAMBOYAN” DI KELURAHAN PANAU KECAMATAN TAWAELI KOTA PALU - Sakina, Siti; Tangkesalu, Dance (AGROTEKBIS, 2018)
This research aims to formulate an appropriate business development and can be applied to the development of banana chipsin the industry "Flamboyan"  in the Panau village Sub District Tawaeli The Palu City. The number of respondents who were interviewed is 5 people chosen from the parties both internal and external. Respondents from the internal parties i.e. 1 person as leader and 1 person as work force of industry "Flamboyan". Respondents from external parties i.e. 2 persons as consumer and 1  owners similar industry or competitors. An analysis of  SWOT analysis is used. Based on the results of internal and external factors weighting can be concluded that the total score obtained from the reduction of total fakor strengths and weaknesses as 1.36 x-axis  While the score of external factors that are the results of the subtraction between opportunities and threats factors factors as y-axis of 1.14. Based on the analysis of SWOT the position  business development strategy of banana chip  Flamboyan  in quadrant I, then the strategy that is focused to the development that is using S-O strategies i.e. maintain chances of increased product demand, promotion strategies and maintain good relationship with distributor. Key Words:Banana Chips, Development Strategy, Flamboyan Enterprises.